2010
DOI: 10.1891/0730-0832.29.5.307
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of NICU Nurses in Caring for Infants with Neonatal Abstinence Syndrome

Abstract: The results suggest that nurses underrate the skill required to care for infants with NAS. The level of knowledge, patience, and commitment to these newborns should be reframed to increase job satisfaction, and education should be offered to nurses about women struggling with addictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 17 publications
0
74
0
Order By: Relevance
“…Saiki et al (2009) and Abrahams et al (2007) reported that the presence of the mother significantly lessened the likelihood of the neonate needing medical intervention for drug withdrawal. Many authors emphasise the importance of the mother's presence during the infant's entire stay in hospital (Murphy-Oikonen et al, 2010;Velez and Jansson, 2008;and Kenner et al, 2000). The mother's presence has been found to reduce the need for treatment, reduce the length of treatment, and increase the speed of the infant's recovery (Murphy-Oikonen et al, 2010;Velez and Jansson, 2008;and Kenner et al, 2000).…”
Section: Does the Presence Of The Infant's Mother Have An Effect On Tmentioning
confidence: 99%
See 4 more Smart Citations
“…Saiki et al (2009) and Abrahams et al (2007) reported that the presence of the mother significantly lessened the likelihood of the neonate needing medical intervention for drug withdrawal. Many authors emphasise the importance of the mother's presence during the infant's entire stay in hospital (Murphy-Oikonen et al, 2010;Velez and Jansson, 2008;and Kenner et al, 2000). The mother's presence has been found to reduce the need for treatment, reduce the length of treatment, and increase the speed of the infant's recovery (Murphy-Oikonen et al, 2010;Velez and Jansson, 2008;and Kenner et al, 2000).…”
Section: Does the Presence Of The Infant's Mother Have An Effect On Tmentioning
confidence: 99%
“…Many authors emphasise the importance of the mother's presence during the infant's entire stay in hospital (Murphy-Oikonen et al, 2010;Velez and Jansson, 2008;and Kenner et al, 2000). The mother's presence has been found to reduce the need for treatment, reduce the length of treatment, and increase the speed of the infant's recovery (Murphy-Oikonen et al, 2010;Velez and Jansson, 2008;and Kenner et al, 2000). Encouraging the mother to touch, hold, talk to and look at her baby not only has positive effects upon the recovery time of infants with NAS, it also improves the infants' responses to sensory stimuli (Kenner et al, 2000).…”
Section: Does the Presence Of The Infant's Mother Have An Effect On Tmentioning
confidence: 99%
See 3 more Smart Citations